Understanding EFL Learners' Experiences with Interactive Exercises for Building Vocabulary Skills - Nor Azizah Riana; Diah Puji Siliwangi; Aghnia Assifa Nadia (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study explores the experiences of English language learners engaging in interactive exercises for the purpose of building vocabulary skills. Understanding learners' experiences with interactive exercises for building vocabulary skills is crucial to inform and enhance teaching methodologies in language education. A qualitative research approach was adopted for this study, wherein interviews were conducted with university students enrolled in English programs. The results show that interactive exercises, such as digital games and group activities, significantly increase the motivation and engagement of students in learning. Participant pointed out that not only did such activities make learning fun, but they also helped them understand acquire more vocabulary. This study pinpoints the importance of incorporating interactive elements into language curricula in order to make the process of learning more dynamic. Emphasizing students' experiences can create an inclusive environment where the students' diverse learning needs are catered for, and this contributes to the improved language proficiency.